2012
DOI: 10.1093/ntr/nts242
|View full text |Cite
|
Sign up to set email alerts
|

Sustainment of Smoking Cessation Programs in Substance Use Disorder Treatment Organizations

Abstract: The majority of individuals who enter substance use disorder (SUD) treatment also use tobacco. Integrating smoking cessation services into SUD treatment may have substantial public health benefits, but few studies have examined whether organizations offering counseling-based smoking cessation programs sustain them over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
28
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 52 publications
7
28
0
Order By: Relevance
“…51 Further, an absence of barriers (e.g., being hospital-based, having a lower number of clinicians who smoked) and the availabilities of incentives (e.g., reimbursement for smoking services) are associated with incorporating pharmacotherapies 52 while support from administrators and building staff expertise have been found to be important for continued success of active smoking cessation services within SUD treatment sites. 53 While more information is needed to build on the research related to SUD treatment programs providing smoking services, research on all aspects of smoking prevention efforts is needed (e.g., the degree to which efforts to prevent smoking initiation are already included in SUD treatment programs, how administrators and staff can develop or build prevention efforts, the most useful content or form of prevention efforts). Improving the ability of SUD treatment programs to provide patients who smoke with treatment access and support and to provide patients who do not smoke with support to remain smoke-free may lead to not just better smoking outcomes but also better outcomes related to illicit drug use.…”
Section: Discussionmentioning
confidence: 99%
“…51 Further, an absence of barriers (e.g., being hospital-based, having a lower number of clinicians who smoked) and the availabilities of incentives (e.g., reimbursement for smoking services) are associated with incorporating pharmacotherapies 52 while support from administrators and building staff expertise have been found to be important for continued success of active smoking cessation services within SUD treatment sites. 53 While more information is needed to build on the research related to SUD treatment programs providing smoking services, research on all aspects of smoking prevention efforts is needed (e.g., the degree to which efforts to prevent smoking initiation are already included in SUD treatment programs, how administrators and staff can develop or build prevention efforts, the most useful content or form of prevention efforts). Improving the ability of SUD treatment programs to provide patients who smoke with treatment access and support and to provide patients who do not smoke with support to remain smoke-free may lead to not just better smoking outcomes but also better outcomes related to illicit drug use.…”
Section: Discussionmentioning
confidence: 99%
“…14 Availability of nicotine replacement therapy in addiction programs decreased over 4 years (from 38% to 34%), 15 and 40% of programs providing cessation counseling in 2006 to 2008 later discontinued this service. 16 According to the 2011 National Survey of Substance Abuse Treatment Services (N-SSATS), only half of all addiction treatment programs screen clients for tobacco use. 17 Three fourths of all addiction treatment is provided in the public sector, 18,19 and regulation and policy setting for these programs are centralized in Single State Agencies for Substance Abuse Services.…”
mentioning
confidence: 99%
“…Similarly, 9% discontinued and 9% adopted at least one pharmacotherapy over the study period (46). A study of sustainment (vs. discontinuation) of counseling-based smoking cessation programs indicated that nearly 40% of those offering such programs at baseline had discontinued such services approximately 36 months later (47).…”
Section: Organizational Studies Of Adoptionmentioning
confidence: 99%
“…In a study focused on the sustainment of counseling-based programs, the odds of sustainment (vs. discontinuation) were greater when the leaders endorsed that smoking cessation was beneficial for SUD recovery and in accredited organizations (47). Worsening of organizational barriers (e.g., lack of skilled staff and lack of staff interest) over time was negatively associated with sustainment (47).…”
Section: Barriers To Adoption and Organizational Characteristicsmentioning
confidence: 99%